Flavin-cyclodextrin conjugates as catalysts of enantioselective sulfoxidations with hydrogen peroxide in aqueous media - Mojr, Viktor; Herzig, Vladimír; Buděšínský, Miloš; Cibulka, Radek; Kraus, Tomáš (Chemical communications (Cambridge, England), 2010)
β-Cyclodextrin-flavin conjugates are highly efficient catalysts for the sulfoxidation of methyl phenyl sulfides with hydrogen peroxide in neat aqueous media operating at loadings down to 0.2 mol% and allowing for enantioselectivities up to 80% ee.
Keywords: beta-Cyclodextrins; Oxidation-Reduction; oxidace-redukce; sulfidy; stereoizomerie; Water; beta-cyklodextriny; Catalysis; Hydrogen Peroxide; Sulfides; peroxid vodíku; flaviny; Flavins; katalýza; voda; Stereoisomerism